Dihydrolipoamide dehydrogenase promotes hepatocellular carcinoma progression and modulates cuproptosis-dependent cell death - Mao-feng Zhong; Yu-yu Guo; Yuan Tian; Tian-xiao Zheng; Lu-yuan Zhu; Juan Du; Wan-fu Lin (Functional & Integrative Genomics, 2026)

Analysis of the AP2/ERF transcription factor family in Eriobotrya japonica and its role in exogenous melatonin-mediated regulation of salt stress - Ling Zhu; Fuhua Liu; Xin Lin; Tianyu Fu; Lin Zou; Yuanhai Pan; Rong Zou; Yang Zhao; Hanyao Zhang (Functional & Integrative Genomics, 2025)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.